Proceedings of the 2nd International Workshop on Systems Development in SOA Environments 2008
DOI: 10.1145/1370916.1370932
|View full text |Cite
|
Sign up to set email alerts
|

Can design pattern detection be useful for legacy systemmigration towards SOA?

Abstract: Legacy systems maintenance involves different decisions, often very complex and sometimes requiring high costs and time. Hence studying and applying the right system modernization technique becomes very important for systems evolution. One of the solutions often adopted to modernize a system is the possibility to migrate it towards a SOA architecture. A lot of works in the literature have been done in this direction, which propose methodologies that provide some kind of migration strategy.In the migration proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Patterns address the design ideas that can be reused in all three migration processes. Examples of these patterns are SOA patterns , design patterns , and architectural styles . Design constraints , which specify a rule or restriction on design elements or provide characteristics of design elements, also shaped SOA migration approaches. We found that using different design constraints such as coupling or cohesion; the migration approaches specify the characteristic of legacy elements that are suitable to be migrated to services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patterns address the design ideas that can be reused in all three migration processes. Examples of these patterns are SOA patterns , design patterns , and architectural styles . Design constraints , which specify a rule or restriction on design elements or provide characteristics of design elements, also shaped SOA migration approaches. We found that using different design constraints such as coupling or cohesion; the migration approaches specify the characteristic of legacy elements that are suitable to be migrated to services.…”
Section: Resultsmentioning
confidence: 99%
“…Another example of such conversion is when existing architecture is transformed to the target service composition (e.g., Arcelli et al . ; Kannan and Srivastava ; Pahl and Barrett ). Not surprisingly, almost all of the primary studies covered this conversion. Externalization of problem‐related to solution‐related knowledge .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are very interested in using such capabilities also in the context of system modernization and in particular for what concerns systems migration to SOA. In this context we have also explored if detecting design patterns in a system can give useful information for the migration of the system towards a Service Oriented Architecture [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we intent to automate the process applied in this paper, for instance the use of the MDA (Model Driven Architecture) or to develop the suitable patterns [10] for the optimization of the migration process. So after the elaboration of a graph of dependences between modules it will be a matter of developing models of transformation intended for an engine for the automatic migration of the existing code towards new architecture based on established conventions.…”
Section: Conclusion and Further Workmentioning
confidence: 99%